Belastungsbedingte klinische und Ultraschallveränderungen in Schultergelenken von Handballspielern - Kruger-Franke, M.; Fischer, S.; Kugler, A.; Rosemeyer, B. (Sportverletzung Sportschaden, 1994)
This prospective clinical and ultrasound study was performed to show specific overuse injuries or changes in the periarticular structures of shoulder joints. Therefore, 11 male handball players with an average age of 23 years and 6 months were evaluated via a standardised shoulder exam sheet and an ultrasound examination before, one hour after, 10-12 hours after, 16-20 hours after and 22-24 hours after specific handball training. Characteristic changes were found in respect of bursitis subacromialis and tendinitis of biceps tendon up to 16-20 hours after training, which were fully reversible 22-24 hours after the stress. The effusion was visible for more than 24 hours after the training but was reversible 60 hours after stress. This study shows characteristic pariarticular changes in the shoulder joint of handball players without any clinical finding in physical examination, so that the ultrasound changes seem to be a physiological reaction to the specific stress. These changes should therefore not be misinterpreted especially if there are no clinical symptoms.